A Passive Flow Control Technique of a Small-Scale HAWT and TED Analysis Under Yaw Condition Based on Airfoil Concavity - Jianlong Ma; Qiuyan Li; Ming Zhao; Yanan Chen; Xiaohui Chai (Energies)
To mitigate the energy loss caused by flow separation of a 300 W small wind turbine, a passive flow control technique based on the airfoil concavity was proposed. The suction surface of the blade was modified with eight different types of concavity, the results showed that the b1 elliptical concavity, with B-spline curves front-and-rear transition, significantly affected the airflow of the airfoil’s suction surface, improving the wind turbine’s aerodynamic performance by 3.26% at maximum. Then, the flow field characteristics of b1, c1, and c4 concave airfoils with typical geometric features under axial flow conditions demonstrated that the b1 airfoil concavity had the greatest impact on flow separation. Moreover, yaw angle was induced, and the wind turbine’s turbulent kinetic energy (TKE) and turbulent energy dissipation (TED) were investigated from the aspects of energy loss. The variation rule of the TED difference between the concave bottom and edge with yaw angle was summarized into an equation that quantitatively explained why the 10° yaw angle was the turning point of the power output, as well as the potential mechanism of concave airfoil-induced power enhancement. These findings provide a foundation for enhancing the aerodynamic performance of large megawatt-class wind turbines.